ANALISIS HUKUM TERHADAP PELAKU TINDAK PIDANA PENYEBARLUASAN PORNOGRAFI MELALUI INTERNET DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Junita Yunara; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The problem of pornography has not been as expected, we can also seethis with the increasingly widespread spread of pornography through the internet.So that the Ministry of Communication and Information of the Republic ofIndonesia said it would block various pornographic websites. People can stillfreely distribute it on their respective social media such as Instagram, Twitter,Facebook and others. Before the existence of special regulations governingpornography itself, contained in Article 282 and 283 of the Criminal Code(KUHP), because there were still many deficiencies in the Criminal Code, LawNo. 11 of 2008 concerning Information and Electronic Transactions was alsodrafted. Law Number 44 of 2008 concerning Pornography.This type of research is normative legal research, known as "legalresearch." In this normative study it is addressed to the law approach. The lawapproach is carried out by examining all laws and regulations relating to legalissues being addressed. Legal research with a legal approach will examine theprinciples of law, reviewing the consistency of regulations relating to theperpetrators of criminal acts of disseminating cyber pornography in theperspective of Indonesian criminal law.In the results of research and discussion there are 3 main problems that canbe concluded. First, the government's efforts to block have not made theperpetrators surrender because even now pornographic content that is spread inthe mass media through the internet is still far from the supervision of thegovernment. Second, existing laws and regulations are still less effective inpreventing and deterring perpetrators of the spread of pornography through theinternet. Third, the problem in the provision of Article 27 Paragraph (1) regardingthe definition of "decency" is that there is no explanation of the meaning ofdecency whether it is the same as the definition of pornography, and themaximum sentence imposed in this article is still in a mild level.Keyword: Legal Analysis, Disseminator, Cyber Pornography.